Zoning map for drought prediction using integrated machine learning models with a nomadic people optimization algorithm - Mohamadi S.; Sammen S.S.; Panahi F.; Ehteram M.; Kisi O.; Mosavi A.; Ahmed A.N.; El-Shafie A.; Al-Ansari N. (Springer, 2023)
algorithm; drought; machine learning; modeling; optimization; prediction; support vector machine; water management; Iran; Euphausiacea